Prospects of Using Foreign Language Texts of Literary Works in Teaching English at the University - Laurensovna Wagner, Monica-Nataliia; Yuryevna Kartseva, Elena; Akparovna Ovezova, Umeda; Vladimirovna Tavberidze, Daria (International Journal of Engineering and Technology, 2018)
At the present stage of the development of society, the need for the transition of the education system to a whole new level has become especially topical. Expanding cooperation with other states and strengthening of external links, the integration of all spheres of life makes foreign languages necessary in real human activities. This significantly changes the status of a foreign language, requiring the training of highly qualified specialists able to navigate the modern world. The relevance of the study is that foreign language literary works contain a significant explicitly and implicitly expressed culturological potential that foreign language teachers can use in the process of teaching a foreign language to students. The purpose of this paper is the analysis of the possibilities of using the cultural potential of works of foreign fiction to expand the language competence of students a significant part of whom will integrate themselves into the world scientific community in the near future. The paper shows that skillsâ€™ development of cross-cultural communication, as well as the language competence of students are the part of the process of reading authentic artistic texts, so that they simultaneously begin to understand the possible difference between their native culture and other cultures, acquire the ability to overcome sociocultural differences taking into account some cultural and regional-specific features of different countries and mastering the common factors of text construction, its functions, and realizing its main lexical-thematic line. At the same time, reading teaching should be carried out taking into account the complexity of the selected texts and simultaneously teaching the recording of the reading, the fulfillment of various creative tasks for inducing independent conclusions and judgments.Â Â